EFFECTIVENESS OF THE APPLICATION OF LEARNING MODELS DEVICE NETWORK APPLICATION INITIATIVE FIELD OF TECHNOLOGY SKILLS INFORMATION AND COMMUNICATION - Purnadi Purnadi; Tri Kuat; Budi Santosa (Journal of Vocational Education Studies, 2018)
Competence of Vocational High School (VHS) students can be qualified, if students have competence in accordance with industry needs. The synchronization of the curriculum with the industry is absolutely necessary, so the school is not left behind by the development of the business world and the industrial world. The development of learning model should always be updated or done curriculum innovation, so that schools can synergize with DUDI. This study aims to (1) to know the implementation of the Device Network Application Initiative learning model, (2) to know the advantages and disadvantages of applying the Device Network Application Initiative learning model, (3) to know the effectiveness of the learning model of the Device Network Application Initiative for the Department of Technology and Information. The learning model of the Device Network Application Initiative (DNA Initiative) (the DNA curriculum) is the application of industrial curriculum to VHS education. Model innovation. The business world and the industrial world (dunia usaha dunia industry/DUDI) are more confident with students who get their learning materials of industry standard. This study uses a qualitative method. The research was conducted by observation, interview and documentation. Data analysis techniques using descriptive analysis techniques. Secondary data in the form of documentation is used to support the research. Focus Group Discussion by presenting DUDI, curriculum experts, industrial class managers, user / user graduates, teachers and testimonials, concluded that the implementation of the Device Network Application Initiative learning model for vocational students is very effective andappropriate. The contribution to schools is the implementation of process concept that schools are industrial environments or industrial replicas.